2015
DOI: 10.1007/s00281-015-0496-2
|View full text |Cite
|
Sign up to set email alerts
|

Protein misfolding and dysregulated protein homeostasis in autoinflammatory diseases and beyond

Abstract: Cells have a number of mechanisms to maintain protein homeostasis, including proteasomemediated degradation of ubiquitinated proteins and autophagy, a regulated process of 'self-eating' where the contents of entire organelles can be recycled for other uses. The unfolded protein response prevents protein overload in the secretory pathway. In the past decade, it has become clear that these fundamental cellular processes also help contain inflammation though degrading pro-inflammatory protein complexes such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 162 publications
(190 reference statements)
0
21
0
Order By: Relevance
“…Genetic mutations in APP, PSEN1 and PSEN2 account for autosomal-dominant AD. 79 Another salient feature of AD is pathological aggregation of the MAPT protein. 80 MAPT is an axonal cytosolic protein for the stabilization of the microtubule network, but it becomes hyperphosphorylated and aggregated within neurons in the form of neurofibrillary tangles.…”
Section: Alzheimer Disease and Other Tauopathiesmentioning
confidence: 99%
“…Genetic mutations in APP, PSEN1 and PSEN2 account for autosomal-dominant AD. 79 Another salient feature of AD is pathological aggregation of the MAPT protein. 80 MAPT is an axonal cytosolic protein for the stabilization of the microtubule network, but it becomes hyperphosphorylated and aggregated within neurons in the form of neurofibrillary tangles.…”
Section: Alzheimer Disease and Other Tauopathiesmentioning
confidence: 99%
“…The autophagy mechanism is a regulated process of ‘self‐eating’, whereby the contents of entire organelles are recycled for other biological functions. Mutations in proteins such as NLRP3 or TNFR1 can overcome normal protein homeostatic mechanisms, resulting in autoinflammatory diseases, such as CAPS and TRAPS . The inflammasomes are at the centre of the pathogenesis of autoinflammatory diseases, so the involvement of autophagy in these conditions may uncover new therapeutic targets.…”
Section: Autophagy and Autoinflammationmentioning
confidence: 99%
“…Likewise, a number of molecular mechanisms have been implicated in the pathogenesis of TRAPS, including abnormal TNF-receptor 1 (TNFR1) receptor cleavage ( 3 ), ligand-independent activation of mutant TNFR1 ( 4 – 6 ), activation of nuclear factor kappa B (NF-κB)/mitogen-activated protein kinase ( 6 – 10 ), generation of mitochondrial reactive oxygen species ( 7 , 11 ), and TNFR1 misfolding and retention within the endoplasmic reticulum (ER), leading to activation of the unfolded protein response (UPR) ( 7 ). This latter cellular stress response appears to be limited to selective activation of the ER-associated endonuclease, inositol-requiring enzyme 1 (IRE1) ( 8 , 12 ); however, this activation can have significant proinflammatory effects as shown by Martinon et al They demonstrated that lipopolysaccharide (LPS) can activate IRE1, via the TLR4 signaling pathway. The spliced X-box binding protein 1 (XBP1) transcription factor, generated via activation of IRE1, can subsequently bind to the promoter regions of TNF and interleukin (IL)-6 ( 13 ).…”
Section: Introductionmentioning
confidence: 99%